Evaluasi Menu A’la Carte Berbasis Menu Engineering Pada The Lounge & Bar Di Hotel Ciputra World Surabaya - Salsabilla, Adinda Maulita; Purwidiani, Niken; Bahar, Asrul; Romadhoni, Ita Fatkhur (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Menu Evaluation aims to evaluate the performance of the a’la carte menu at The Lounge & Bar, Hotel Ciputra World Surabaya, utilizing the menu engineering approach. The analysis encompasses 60 food items and 93 beverage items over the period from July to September 2024. Menu engineering is a data-driven method that assesses each menu item's popularity and profitability, facilitating strategic decisions regarding menu optimization.​ Employing a quantitative descriptive methodology, data were collected through direct observation, interviews with restaurant management, and sales data analysis. Each menu item was classified into one of four categories:​ Star, High popularity and high profitability. Plowhorse, High popularity but low profitability. Puzzle, Low popularity but high profitability. Dog, Low popularity and low profitability. The analysis revealed that items such as french fries and nasi goreng nusantara fall into the Star category, indicating both high sales and profit margins. Dishes duck spring roll and oxtail soup are categorized as Puzzle, suggesting they are profitable but not popular. calamari rings and chicken wings are identified as Plowhorse, being popular yet yielding lower profits. Conversely, fried platter and onion rings are classified as Dog, reflecting low sales and profitability.